Coupling and Interlayer Exciton in Twist-Stacked WS2 Bilayers - Zheng, Shoujun (2016)
Interlayer electronic and mechanical couplings of transitional metal dichalcogenides (TMDs) due to Van der Waals force determine their band structure and Raman modes evolution, respectively. We have synthesized twist-stacked WS2 bilayers with twist angles of 0°, 13°, 30°, 41°, 60°, and 83° via chemical-vapor deposited, which allows us to study the coupling effect by Raman and photoluminescence spectroscopy and density function calculation. The photoluminescence property implies that these random-twisted WS2 bilayers behave as quasidirect bandgap material due to weakened interlayer coupling as a result of larger interlayer distances than the non-twisted 0° and 60° stacked WS2 bilayers (with an indirect band gap). In addition, an additional small peak (AI) near the excitonic transition peak (A) is observed from the twisted bilayers, which can be attributed to the interlayer exciton transition.